Paul Russell: the transcendentalist surgeon of America - Abdi, Reza (Frontiers in Transplantation, 2023)
I first met Dr. Russell in the Fall of 2000 at the Massachusetts General Hospital (MGH). Once I entered in the Russell-Round-Room which was packed with surgeons and physicians of MGH, among whom there was no shortage of self-esteem. I came across a handsome man, full of vigor and competence, standing still for nearly two hours in the corner of the room near the blackboard. He was remarkably attentive to the questions, for which he had very concise responses. He was soft-spoken with an inviting smile, and had a welcoming, modest air about him. Despite his remarkable academic achievements, he was strikingly unassuming and serene -- features likely ingrained in his very nature.